A study on the distribution coefficient of iodide ions from aqueous solution on some strongly basic anion exchange resins. (12th October 2009) - Singare, P.U.; Lokhande, R.S.; Parab, S.A.; Patil, A.B.
The ion exchange resins Duolite A-116, Indion 830 Type-1 and Indion N-IP Type-2 in iodide form were equilibrated separately with labelled radioactive iodide ion solutions of different concentrations varying from 0.005 M to 0.020 M in the temperature range of 25.0°C to 40.0°C. The Kd values of iodide ions for Duolite A-116 and Indion N-IP Type-2 were higher than that for Indion 830 Type-1 under identical experimental conditions. The difference in the Kd values of iodide ions for the three resins was mainly because of the swelling pressure, which depends on their water-holding capacities.